ASSESSMENT OF GROUNDWATER QUALITY FOR IRRIGATION USING WATER QUALITY INDEX (IWQ INDEX) IN AL-KASIK SUBDISTRICT NORTHWESTERN, IRAQ (Nigerian Journal of Technology, 2020)
This research work analysed groundwater quality in Al-Kasik district northeastern of Mosul city, Iraq. The area is agricultural land which uses well water for livestock watering and irrigation. Groundwater samples were collected from five wells during dry season to determine the following parameters: pH, electrical conductivity (EC25,), anions, cations, soluble sodium percentage (SSP), sodium absorption ratio (SAR), residual sodium carbonate (RSC) and potential salinity, permeability index and Kelly Ratio, IWQ index model was applied for the evaluation. The well water samples were evaluated for agricultural uses according to universal standard classification. Results indicated that most of the measured parameters were high especially electrical conductivity (5369µS/cm), with P. Salinity, Sodium, Calcium and Sulfate ions having 30.7, 15.3, 34.0, 29.3 meq. l-1 respectively. These have an effect on water quality hence considered being of very high salinity (C4) according to United State Salinity Laboratory (USSL). According to the water quality index (IWQ index), the analyzed water was specified as low restriction (LR) to Severe restriction (SR) for irrigation. http://dx.doi.org/10.4314/njt.v39i1.35